Peningkatan Kemampuan Anak Mengenal Geometri Melalui Permainan Balok Geometri Berpasangan di Tk Taratak Minang Pasaman Barat Sumatera Barat - Jummiati Jummiati; Isti Komariyah; Destri Warni (Jurnal Pendidikan Tuntas, 2023)
Children's ability to recognize geometric shapes is still low, the purpose of this study is to improve children's ability to recognize geometry through geometry block games in pairs. This research uses Classroom Action carried out at Taratak Minang Kindergarten West Pasaman with a total of 20 children, consisting of 10 boys and 10 girls. Data collection by observation, interview, and documentation was analyzed by percentage technique. The research was conducted in 2 cycles, each cycle consisted of: Planning, Implementation, Observation, and reflection. The results of the research in each cycle have improved children's ability to recognize geometry after action in cycle II. Based on the results of the actions that have been carried out can be concluded that the increase in the ability to recognize the geometry of children through the game Paired geometry blocks, before the action of the child's ability is still low in children who get a very high score, after the action has increased then the game Paired geometry blocks have succeeded in improving children's ability to recognize geometry. Keywords: Recognizing Geometry, Geometry Block Game, Classroom Action Research